Dispersal and local persistence shape the genetic structure of a widespread Neotropical plant species with a patchy distribution - Santos Leal, Barbara Simoes [UNESP]; Graciano, Vanessa Araujo [UNESP]; Neves Chaves, Cleber Juliano [UNESP]; Pillaca Huacre, Luis Alberto; Heuertz, Myriam; Palma-Silva, Clarisse [UNESP] (Oxford Univ Press, 2019)
Background and Aims Isolated populations constitute an ideal laboratory to study the consequences of intra-specific divergence, because intrinsic incompatibilities are more likely to accumulate under reduced gene flow. Here, we use a widespread bromeliad with a patchy distribution, Pitcairnia lanuginosa, as a model to infer processes driving Neotropical diversification and, thus, to improve our understanding of the origin and evolutionary dynamics of biodiversity in this highly speciose region. Methods We assessed the timing of lineage divergence, genetic structural patterns and historical demography of P. lanuginosa, based on microsatellites, and plastid and nuclear sequence data sets using coalescent analyses and an Approximate Bayesian Computation framework. Additionally, we used species distribution models (SDMs) to independently estimate potential changes in habitat suitability. Key Results Despite morphological uniformity, plastid and nuclear DNA data revealed two distinct P. lanuginosa lineages that probably diverged through dispersal from the Cerrado to the Central Andean Yungas, following the final uplift of the Andes, and passed through long-term isolation with no evidence of migration. Microsatellite data indicate low genetic diversity and high levels of inbreeding within populations, and restricted gene flow among populations, which are likely to be a consequence of bottlenecks (or founder events), and high selfing rates promoting population persistence in isolation. SDMs showed a slight expansion of the suitable range for P. lanuginosa lineages during the Last Glacial Maximum, although molecular data revealed a signature of older divergence. Pleistocene climatic oscillations thus seem to have played only a minor role in the diversification of P. lanuginosa, which probably persisted through adverse conditions in riparian forests. Conclusions Our results imply drift as a major force shaping the evolution of P. lanuginosa, and suggest that dispersal events have a prominent role in connecting Neotropical open and forest biomes.
Keywords: Bromeliads; dispersal events; Neotropical diversification; Central Andean Yungas; Cerrado; genetic drift; phylogeography; Pitcairnia lanuginosa Ruiz & Pav; riparian forests